comprehensive study based on societal question and answer system using natural language processing with topic modelling for job assistantship in the world industry - Rani, K. Pushpa; Latha, P. Vidyu; Rao, K. Srinivas (International journal of health sciences, 2022)
This breakthrough study explores public opinion on technical words or topics using data from social media. Individuals seeking work assistance must consider public opinion on the existence of terminological or technical obstacles, as well as their impact on the environment and society. Public assistance is also required for the execution of legislation and mitigation programmes. A public opinion study is required to better understand the social environment and social processes. Researchers are paying special attention to social media data because it provides extremely significant information on public perceptions and responses to conflicting socio-technical terminology or issues, such as quorums, stack overflows, and yahoo! It also responds to Twitter and other social media platforms, and it's frequently used to monitor and analyze how society reacts to natural and social calamities. Search for keywords or topics in topic models to identify distinct topics to get the most out of social media data. In classic topic models, users may provide an erroneous number of subjects, resulting in unsatisfactory grouping results. For data retrieval and cluster trend identification in these scenarios, exact representations are essential.